Impact and memory of Ortega y Gasset in Ferrater Mora - Naji Mehmet (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2019)
In this contribution, the interpretation that José Ferrater Mora made of the work of the philosopher José Ortega y Gasset is exposed for the first time. After offering a brief intellectual profile of the Catalan thinker, his correspondence with Ortega y Gasset is studied below, also analyzing all of Ferrater's writings on Ortega, to conclude that, in Ferrater Mora's opinion, Ortega y Gasset is a "Living thinker" who always comes back.